ChemInform Abstract: Efficient Synthesis of 3H‐Indoles Enabled by the Lead‐Mediated α‐Arylation of β‐Ketoesters or γ‐Lactams Using Aryl Azides. Issue 48 (2nd December 2014) - Zhou, Fei; Driver, Tom G.
Abstract A simple protocol for the α‐arylation of various β‐ketoesters and lactam (IX) using 2‐azidoaryllead acetates to yield functionalized aryl azides is developed.